EVALUATION OF THE ROLE OF CHITOSAN IN THE IMMUNOPATHOLOGY OF OSTEOMYELITIS IN DIABETIC RABBITS (Basrah Journal of Veterinary Research)
This study was conducted to investigate the beneficial effects of chitosan in the immunopathology of osteomyelitis in diabetic rabbits; therefore, the experimental design was carried out on 40 rabbits. They were  divided into 5 groups each of 8 animals, diabetes mellitus was induced in rabbits , then infected by Staphylococcus aureus and treated as following: First group (G1) was induced diabetes mellitus then immunized by whole sonicated S. aureus antigens (WSSAG) and induced experimentally osteomyelitis. The second group (G2) was induced diabetes mellitus, then immunized by (WSSAG) and induced experimentally osteomyelitis and fed on diet containing chitosan. Third group (G3) was induced diabetes mellitus, and induced experimentally osteomyelitis only. Fourth group (G4) was induction of diabetes mellitus, and induced experimentally osteomyelitis and fed on diet containing chitosan. Fifth group (G5) was induced experimentally osteomyelitis only without diabetes mellitus induction. Then at day 28th - 30th post immunization, skin test was performed to each of the immunized groups, and at day 30th the antibodies titer was measured by passive hemagglutination assay and phagocytic activity, then the animals were sacrificed and the treated bone taken for histopathological examination. In the present study , a significant increase was noted in the value of skin thickness of G2 at 48 and 72 hrs PI.  A significant increase was also noted in the value of antibodies titers of G2. We also showed a marked decrease   in the t1/2 of carbon clearance of G2. The histopathological results of G2 showed normal periosteal surface and compact bone with active osteoblasts lining the trabecular bones 30 days PI. However, other groups showed many histopathological lesions like infiltration of inflammatory cells and proliferation of fibrous connective tissue in G1, G3, and G4.The results also showed necrotic bone, hemorrhage, inflammatory cells infiltration and fibrosis in G5. Taken together, these findings indicate that the chitosan had a beneficial effect in bone healing of diabetic animals after infection in S. aureus.